Does drought stress modify the effects of plant‐growth promoting rhizobacteria on an aboveground chewing herbivore?. (25th July 2017) - de Bobadilla, Maite Fernández; Friman, Julia; Pangesti, Nurmi; Dicke, Marcel; van Loon, Joop J.A.; Pineda, Ana
Abstract: Soil microbes have important effects on the interactions of plants with their environment, by promoting plant growth, inducing resistance to pests or by conferring tolerance to abiotic stress. However, their effects are variable and the factors responsible for this variation are mainly unknown. Our aim was to assess how drought stress modifies the effect of the nonpathogenic rhizobacterium Pseudomonas simiae WCS417r on plant growth and resistance against the generalist leaf‐chewing caterpillar Mamestra brassicae . We studied Arabidopsis thaliana Col‐0 plants, as well as mutants altered in the biosynthesis of the phytohormones jasmonic acid (JA) and abscisic acid (ABA). Caterpillars did not prefer rhizobacteria‐treated plants, independently of drought stress. Rhizobacteria colonization had a variable effect on caterpillar performance, which ranged from positive in one experiment to neutral in a second one. Drought had a consistent negative effect on herbivore performance; however, it did not modify the effect of rhizobacteria on herbivore performance. The effect of drought on herbivore performance was JA‐mediated (confirmed with the use of the dde2‐2 mutant), but it was still present in the ABA‐deficient mutant aba2‐1 . Plant biomass was reduced by both drought and herbivory but it was enhanced by rhizobacterial colonization. Pseudomonas simiae WCS417r is able to promote plant growth even when plants are suffering herbivory. Nevertheless, the microbial effect on the herbivore is variable, independently of drought stress. To get the best possible outcome from the rhizobacteria‐plant mutualism it is important to understand which other factors may be responsible for its context‐dependency.